Association between the atherogenic index of plasma and non-alcoholic fatty liver disease in Korean pregnant women: secondary analysis of a prospective cohort study - Shuai, Rong; He, Yuxing; Yang, Dongqian; Zhang, Yingying; Zhang, Li (Frontiers in Nutrition, 2025)
BackgroundRecent studies have shown an association between atherogenic index of plasma (AIP) and nonalcoholic fatty liver disease (NAFLD), but the association in a population of pregnant women remains unclear.ObjectivesOur study aimed to examine the association between AIP and NAFLD in pregnant Korean women.MethodsOur study used publicly available data from Korea, which recruited singleton pregnant women between November 2014 and September 2016 who were at 10–14 weeks of gestation. The presence of NAFLD was diagnosed by liver ultrasound. AIP was calculated as log10 (TG/HDL). Participants were grouped according to AIP tertile: T1 (< 0.16, n = 195), T2 (0.16–0.32, n = 195), and T3 (>0.32, n = 196). Logistic regression models were used to estimate the relationship between AIP and NAFLD. Subgroup and sensitivity analyses were conducted to explore the stability of this relationship. Restricted cubic spline (RCS) curve fitting was employed to investigate potential non-linear associations.ResultsAfter excluding data on missing variables, 586 singleton pregnant women were finally included. The subjects included in the study had an average AIP of 0.22 (0.11, 0.37), and NAFLD occurred in 110 (18.8%) pregnant women. We observed a positive linear association between AIP and NAFLD (OR = 1.33, 95% CI: 1.19–1.48), which persisted after adjusting for potential confounders (OR = 1.2, 95% CI: 1.06–1.37). When AIP was used as a categorical variable, after adjusting for covariates, the NAFLD risk was significantly higher in the highest tertile of AIP than in the lowest group (OR = 2.02, 95% CI: 1.11–3.68). Their correlations were stable across subgroups and sensitivity analyses.ConclusionIn this secondary analysis of a prospective cohort study of pregnant Korean women, AIP was found to be positively associated with NAFLD. These outcomes might be used to screen for NAFLD in pregnant women.